2001
DOI: 10.1523/jneurosci.21-12-04427.2001
|View full text |Cite
|
Sign up to set email alerts
|

Forced Limb-Use Effects on the Behavioral and Neurochemical Effects of 6-Hydroxydopamine

Abstract: Rats with unilateral depletion of striatal dopamine (DA) show marked preferential use of the ipsilateral forelimb. Previous studies have shown that implementation of motor therapy after stroke improves functional outcome (Taub et al., 1999). Thus, we have examined the impact of forced use of the impaired forelimb during or soon after unilateral exposure to the DA neurotoxin 6-hydroxydopamine (6-OHDA). In one group of animals, the nonimpaired forelimb was immobilized using a cast, which forced exclusive use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
248
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 325 publications
(267 citation statements)
references
References 91 publications
15
248
0
2
Order By: Relevance
“…The bar test essentially measures the time to initiate a movement (akinesia), whereas the drag test measures both the time to initiate and to execute it (bradykinesia). The degree of motor asymmetry in the drag test (ϳ65%) was consistent with that reported by Wessell et al (2004) (ϳ75%) and in line with that found with the stepping [ϳ90% (Olsson et al, 1995); 80 -90% (Winkler et al, 2002); ϳ70% (Tillerson et al, 2001); ϳ75% (Tseng et al, 2005); 50 -90% (Kelsey et al, 2004)] or the postural adjustment [ϳ75% (Lindner et al, 1996); Ͼ95% (Chang et al, 1999)] tests. Powerful, dose-dependent attenuation of parkinsonism was produced by increasing L-DOPA doses: reduction of akinesia at both the ipsilateral and the contralateral forepaw (0.1 mg/kg), improvement of exercise-induced motor performance (0.3 mg/kg), and reversal of motor asymmetry both under resting (bar test) and dynamic (drag test) conditions (6 mg/kg).…”
Section: J-113397/l-dopa Interaction On Behaviorsupporting
confidence: 91%
“…The bar test essentially measures the time to initiate a movement (akinesia), whereas the drag test measures both the time to initiate and to execute it (bradykinesia). The degree of motor asymmetry in the drag test (ϳ65%) was consistent with that reported by Wessell et al (2004) (ϳ75%) and in line with that found with the stepping [ϳ90% (Olsson et al, 1995); 80 -90% (Winkler et al, 2002); ϳ70% (Tillerson et al, 2001); ϳ75% (Tseng et al, 2005); 50 -90% (Kelsey et al, 2004)] or the postural adjustment [ϳ75% (Lindner et al, 1996); Ͼ95% (Chang et al, 1999)] tests. Powerful, dose-dependent attenuation of parkinsonism was produced by increasing L-DOPA doses: reduction of akinesia at both the ipsilateral and the contralateral forepaw (0.1 mg/kg), improvement of exercise-induced motor performance (0.3 mg/kg), and reversal of motor asymmetry both under resting (bar test) and dynamic (drag test) conditions (6 mg/kg).…”
Section: J-113397/l-dopa Interaction On Behaviorsupporting
confidence: 91%
“…The use of each forelimb for weight support or weight shifting along the walls is examined using slow motion video recordings. [21][22][23][24] An experienced investigator can accurately score the data live, however. The test is sensitive to long-term deficits in forelimb use that might otherwise be masked by motor learning, and the scores do not change with repeated testing.…”
Section: Forelimb Use For Vertical-lateral Explorationmentioning
confidence: 99%
“…Vibrissae-elicited forelimb placing (placing test)-This test has been well described and utilized to measure 6-OHDA-elicited deficits [35,39,44]. Additionally, thrombin preconditioning has been found to provide protection from 6-OHDA-elicited deficits in this test [3].…”
Section: Neurobehavioral Assessmentmentioning
confidence: 99%
“…utilized to assess 6-OHDA-elicited deficits [35,39] and also protection elicited by preconditioning in this model [3,39]. Briefly, the animal was placed in a clear plastic cylinder (height: 30 cm, width: 20 cm) and forelimb asymmetry was determined during rearing behavior.…”
Section: Forelimb-use Asymmetry During Rearing (Asymmetry Test)-this mentioning
confidence: 99%